A Pre-Experimental Study to Assess the Effectiveness of Video Assisted Teaching Programme on Knowledge Regarding Health Hazards of Using Mobile Phone Among School Going Children of Selected Schools of District Kangra, Himachal Pradesh (International Journal of Nursing Education, 2022)
Background: School going children represents a period of transition between childhood and adulthood. In recent years, adoption of mobile phones by school going children has been a global phenomenon. Several studies revealed that during use mobile phone and cordless phone emit radiofrequency (RF) radiation that can possibly cause cancer and long-term health issues. Therefore, children need awareness regarding health hazards of using mobile phone.Material and methods: A quantitative research approach and pre-experimental research design was adopted to conduct study. The non-probability purposive sampling technique were used to select 60 school going children of District Kangra, Himachal Pradesh. A Self-structured knowledge questionnaire was used to assess knowledge score. Analysis of collected data was done according to the objectives of the study and data analyzed by using descriptive and inferential statistics.Results: The mean pre-test knowledge score was 14.53 where 70% school going children were having moderately adequate knowledge, 25% were having inadequate knowledge and only 5% were having adequate knowledge. Whereas the mean post-test knowledge score was 20.77 where 55% were having adequate knowledge, 43.33% were having moderately adequate knowledge and only 1.67% having inadequate knowledge. Hence, results revealed that the post-test knowledge score (20.77) was significantly higher than pre-test (14.53) and obtained ‘t’ value has been found statistically very highly significant (8.458) at p
Keywords: Mobile phone, Health hazards, School going children, Video assisted teaching program.